Teaching and Learning Online During the COVID19 Pandemic in Malaysia: Challenges, Motivation, and Lessons from the Hadith "Man Salaka Tariqan" - Muhammad Zulkifli Bin Nor Azib; Helimy Bin Aris; Walid Bin Mohd Said; Abdullah Muiz Bin Mohd Zaki; Ibrahim Adham Afif Bin Ismail; Mustakim Muslim Bin Yubaithullah (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2024)
International Journal of Academic Research in Business and Social Sciences, Volume 14 Issue 8 Page (2975–2983)